Commuting Women Farm Labourers: Multiple Loads And The Marginalisation Of Minangkabau Women In Rural Areas - Suasti, Yurni; Fatmariza, Fatmariza; Montessori, Maria; Aulia Putri, Egi (Opción, 2019)
This article aims to describe the phenomenon of the Minang women’s life as farm workers who work every day in a neighbouring village which is about 10 to 15 km away. This study used a case study qualitative approach. The data was collected through interviews, observations and documentation studies. The informants consisted of 10 female farm labourers, families, brokers, and community leaders. The results of the study show that female farm workers, both single and married, have a double burden as women. Workplaces that are far from their homes mean that the female farm labourers work early at home to prepare everything that their family members need for the day. In addition, their considerable distance from the workplace also demands that female farm labourers “willingly” jostle in “cheap” transportation to go be- tween work and the home in a state of insecurity. Their wages are relatively cheap compared to the local village farm workers. Women are also increas- ingly encouraged to become commuter workers. For some groups, female workers are organised by brokers in their original villages. This phenomenon illustrates the complexity of the problems of rural Minang women today in that they are increasingly far from a high position and there is no guarantee of social protection in the matrilineal kinship system.